Effect of spent mushroom compost on yield and fruit quality of tomato (Asian Journal of Medical and Biological Research, 2016)
An experiment was conducted to observe the performance of the composted spent mushroom substrate (SMS) along with chemical fertilizers on the yield, fruit quality and nutrient uptake by tomato plant for using the mushroom waste through composting. The experiment was laid out in a randomized complete block design with seven replications. Treatments were T1: no fertilizer and compost application (control), T2: recommended dose of fertilizers (RFD), T3: 25% SMC-N+ 75% fertilizer-N, T4: RFD + 2.5 t ha-1 SMC, T5: 50% SMC-N + 50% fertilizer-N, T6: 100% SMC-N and T7: 100% SMC-N + 50% fertilizer-N. Application of SMS compost at 2.5 t ha-1 along with recommended fertilizer dose showed the best performance for number of fruits, fruit yield, fruit quality (total protein, vitamin C, total sugar, reducing sugar) and nutrient uptake by tomato. This treatment showed significantly higher fruit yield, quality and nutrient uptake not only over control but also RFD, SMS compost alone and combination of SMS compost & RFD. Though SMS compost alone proved less effective, however combined application of SMS compost at 2.5 tha-1 with chemical fertilizer of recommended dose had shown to be more effective.Asian J. Med. Biol. Res. December 2015, 1(3): 471-477